Functional analysis of an ubiquitin fusion degradation protein gene UFD1 in regulation of plant disease and stress resistance - LAI Yi-yu; LI Fei; XU You-ping; CAI Xin-zhong (浙江大学学报. 农业与生命科学版, 2012)
A fragment of ubiquitin fusion degradation protein (UFD) gene UFD1 was cloned from tomato by reverse transcription-polymerase chain reaction (RT-PCR), and its role in regulation of plant disease and stress resistance was analyzed employing virus-induced gene silencing (VIGS) technique. The results showed that the silencing of UFD1 in Nicotiana benthamiana resulted in significantly weakening of hypersensitive response (HR) mediated by Cf-4/Avr4- and Cf-9/Avr9 and induced by Xanthomonas oryzae pv. oryzae (Xoo), alleviating of necrotic symptoms of tobacco wild fire disease, decreasing of chlorophyll content in leaves under stress of high concentration of salt, but did not lead to change of symptoms of white mould disease caused by Sclerotinia sclerotiorum and resistance to drought stress. It is indicated that UFD1 is a pivotal regulator of plant disease and stress resistance, playing roles in positive regulation of Cf-4- and Cf-9-dependent gene-for-gene resistance, nonhost resistance to Xoo and salt tolerance, and in contrast, negative regulation of resistance to tobacco wild fire disease.